STUDI KRITIS TERHADAP STRATEGI PENGEMBANGAN SUMBER DAYA MANUSIA PADA STEI HAMFARA - Sugeng Nugroho Hadi (At-Tauzi : Jurnal Ekonomi Islam, 2015)
Research with the title "Critical Study of Human Resource Development Strategies at STEI Hamfara" is intended to explain how the human resource development strategy at STEI Hamfara. This study is important considering that human resources at one educational institution or at another business institution occupies a central position in its operations.There are two groups of human resources or personnel at STEI Hamfara, namely educational staff (lecturers) and education staff (employees). Strategically the development of lecturer HR is directed at the "qualified" position while the employees are directed at the "dedicative" position. Through qualitative studies with primary data supported by observation and secondary data in the form of STEI Hamfara's internal official documents and literature, critical studies are carried out using content analysis techniques.It was concluded that the human resource development strategy of STEI Hamfara which is by system is considered to be very effective in growing qualified commitment to lecturers and dedication to employees